1994
DOI: 10.2508/chikusan.65.217
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Changes in Rumen Fermentation and Blood Properties in Holstein Steers Fed a Concentrate Mixture for Fattening and Rolled Barley

Abstract: Three rumen-fistulated Holstein steers were given a high roughage diet (R) and three kinds of high concentrate diet consisting of 10kg of a concentrate mixture for fattening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…There is a high positive correlation between chewing time and secretion of saliva (Erdman 1988). Obara et al . (1994) reported that rumen function was maintained in good condition despite the small 6.5 ± 0.6 6.9 ± 0.4 6.1 ± 0.4 6.6 ± 0.3 NS NS NS 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a high positive correlation between chewing time and secretion of saliva (Erdman 1988). Obara et al . (1994) reported that rumen function was maintained in good condition despite the small 6.5 ± 0.6 6.9 ± 0.4 6.1 ± 0.4 6.6 ± 0.3 NS NS NS 9…”
Section: Discussionmentioning
confidence: 99%
“…There is a high positive correlation between chewing time and secretion of saliva (Erdman 1988). Obara et al . (1994) reported that rumen function was maintained in good condition despite the small amount of long rice straw provided (only 6% of the total diet) on the high concentrate diets, and discussed that the long rice straw (approximately 60 cm length) was able to provide sufficient mechanical stimulation to the upper digestive tract to maintain the digestive functions of the ruminant such as rumen motility, salivary secretion and the eructation reflex.…”
Section: Discussionmentioning
confidence: 99%